ISLAMIC ETHICS BASED ON AL-QUR'AN AND MULLA ṢADRĀ’S ESCATOLOGY - Kerwanto Kerwanto (Teosofia: Indonesian Journal of Islamic Mysticism, 2015)
Mulla Ṣadrā is one of the philosophers who provide philosophical views and answers to the principles of eschatology (ma'ād) that have not been answered by the philosophers of his predecessors. He is also known for successfully pouring his philosophical thoughts in his various commentaries on the main religious sources, both those relating to the Qur'an and ḥadīth. In this paper, there are several principles of eschatology of Ṣadrā which the writer will examine as the position of Ṣadrā in regard to post-mortal physical resurrection, the intellectual (intellectual) (intellectual), the role of the Actor (fā'il) and Action ('amal) and the relationship between resurrection (ma'ād) and ethics (Akhlāk). In the eschatology of Ṣadrā, the knowledge of eschatological matters (life akherat) has a major influence on an individual's ethical actions. This paper is also intended to show that Mulla Ṣadrā's ethics as an implication of his eschatological philosophy is synergistic with the main sources of religion; Both the Qur'an and the Hadith of the Prophet.